Respuesta :
The answer is: " 56x + 896 " .
____________________________________
First, simplify the:
(x + 12 + 4) = (x + 16) ;
56(x + 12 + 4) =
56(x + 16) ;
_________________________
Note the distributive property of multiplication:
a(b + c) = ab + ac ;
a (b - c) = ab - ac ;
_________________________
So;
_________________________
56(x + 16) =
56*x + 56*16 =
56x + 896
________________________
____________________________________
First, simplify the:
(x + 12 + 4) = (x + 16) ;
56(x + 12 + 4) =
56(x + 16) ;
_________________________
Note the distributive property of multiplication:
a(b + c) = ab + ac ;
a (b - c) = ab - ac ;
_________________________
So;
_________________________
56(x + 16) =
56*x + 56*16 =
56x + 896
________________________